Removal of scale deposition on pipe walls by using magnetic field treatment and the effects of magnetic strength - Sohaili, J. (Elsevier Ltd, 2016)
Scale deposition on pipe walls is prevalent in water distribution systems and is difficult to remove. Commonly, chemical treatment is applied to remove the hard scale. However, it is detrimental to users' health and causes adverse environmental impacts. The need for clean water production for potable and other applications is essential. This study shows the application of magnetic water treatment as a safe and effective method for scale removal in water purification. Permanent magnets were installed in the designed treatment devices that consisted of pipes with scale deposition and the effect of magnetic field on scale reduction was monitored. The scale removal efficiency was evaluated based on calcium concentration in the outlet, after passing through the magnetic field. Magnetic strength was varied between 0.1 T to 0.4 T to investigate its effect on scale reduction. The morphology were analyzed by field emission scanning electron microscope. It was found that magnetic field enhanced scale removal from pipe walls by 46.7. With respect to the increasing the magnetic field strength to 0.4 T, the efficiency of removal also increased to 30. Possible mechanisms involved in the magnetic treatment that affects scale reduction such as the effect of magneto-hydrodynamics and magnetically modified hydration are discussed. Magnetic technology is a simple, cost-effective and environmentally friendly treatment approach for clean water production with significant scale removal efficiency. Magnetic treatment can be used either as a stand-alone technology or in water purification systems. Â© 2016 Elsevier Ltd